Water Splitting: Computational Screening of 2D Materials and Rational Design of Heterojunctions for Water Splitting Photocatalysts (Small Methods 5/2018). Issue 5 (9th May 2018) - Zhang, Xu; Zhang, Zihe; Wu, Dihua; Zhang, Xin; Zhao, Xudong; Zhou, Zhen
Abstract : A high‐throughput computational materials‐design framework is proposed by Zhen Zhou and co‐workers in article number1700359 to search for layered photocatalysts for water splitting from the Materials Project database. From layered compounds to 2D monolayers and then to heterojunctions, the quantum efficiency and photocatalytic performance can be gradually enhanced.